Research of the design feasibility of a 3-wheel electric vehicle with a simplified control system - Medić, Srđan (Array, 2020)
The need for a simple, customised electric vehicle (EV) has inspired the research of the possibility to build a simple EV tailored for the specific needs of the buyer. This paper is focused on the concept of an EV with no conventional control mechanism. In this paper, a research of user needs, vehicle dynamics, vehicle aerodynamics, type of drive and batteries was carried out. EV aerodynamics characteristics were simulated by using the Computational Fluid Dynamics (CFD) software. The control system was designed in correlations with the maximal safe velocity and the radius of EV turning on a circular path. The stability of the EV, concerning the vehicle turning over and wheels slipping while driving in the curves, was the main concern of this paper. The steering wheel and brake pad were replaced with a control stick. Using the Finite Element Method (FEM) analysis, key parts of the construction were constructed.